Prolonged dengue viremia with predominantly ocular manifestations in a lung transplant recipient - Leong Shuen Loo; Michael Zhang; Jane Wells; Noor Ali; Ian Marr (BMC Infectious Diseases)
Abstract Background The clinical manifestations of dengue are well-described, but ocular involvement is being increasingly recognized and alterations to the natural trajectory of disease, including protracted viraemia, have also been recognized in immunocompromised patients. We describe a case of dengue in a lung transplant recipient which manifested predominantly as ocular symptoms following short-lived systemic features, and with protracted viraemia with delayed IgM to IgG seroconversion. Case presentation A 40-year-old woman who had a bilateral lung transplant 15 years prior for cystic fibrosis presented with headaches, bilateral scotomata and rapidly deteriorating visual acuity. She had recently travelled to Bali where she experienced a short-lived febrile illness featuring a retro-orbital headache and generalized arthralgia. Ocular examination demonstrated bilateral cystoid macular oedema, retinitis and retinal vasculitis. Dengue serotype 1 RNA was detected in serum, urine and aqueous humour samples. Dengue serology showed positive NS1 and IgM, and negative IgG. She had presented 14 days after the initial febrile illness began. High-dose prednisolone was commenced for the macular oedema, but this was stopped when low-grade fevers and arthralgias developed. Her immunosuppression was reduced, with clinical improvement to visual acuity and macular oedema observed, but high-dose prednisolone was recommenced at day 36 of illness due to new retinal haemorrhages, this time well-tolerated, with subsequent dose tapering. Viraemia was protracted, clearing at day 69, and IgG seroconversion was noted on day 319. Her vision improved sufficiently to allow driving and return to part-time work, though she continues to experience persisting symptomatic right-sided macular oedema. Conclusions This was an unusual presentation of dengue involving an immune-privileged site in an immunocompromised host. The competing priorities of facilitating immune-mediated clearance of viraemia versus controlling ocular inflammation posed a significant therapeutic challenge. A greater understanding of the pathophysiology of dengue eye disease, including virus-mediated and immune-mediated factors, as well as the development of therapeutic options, is critically required.